STUDY OF PREVALENCE AND SUSCEPTIBILITY PATTERN OF METHICILLINRESISTANT STAPHYLOCOCCUS AUREUS (MRSA) AT SREE GOKULAM MEDICAL COLLEGE, TRIVANDRUM. - ASHISH J; VINAY H (International Journal of Pharma and Bio Sciences, 2013)
Methicillin-resistant Staphylococcus aureus (MRSA) one of the most widespread causes of nosocomial infection’s worldwide. Recently, they have been recovered from community. This study was undertaken to analyze the prevalence of methicillin resistance among isolates at Sree Gokulam Medical College,Trivandrum, and document the current resistance profile of MRSA and methicillin-sensitiveStaphylococcus aureus (MSSA) to the commonly used anti-staphylococcal agents. Over a 2-year period we analyzed 1215 isolates of S. aureus strains recovered from various clinical sources, from hospital and community practices. Antimicrobial susceptibility testing was done according to CLSI guidelines. The prevalence of MRSA from surgical/burn wounds/pus, urine and miscellaneous others were 60.1%, 15.5% and 6.6%, respectively. The major sources of MSSA were surgical/burn wounds, pus/abscess and upper respiratory tract specimens with rates of 32.9%, 17.1% and 14.3%, respectively. The greatest prevalence of resistance of MRSA along with beta lactams was seen for erythromycin (86.7%), and clindamycin (70%). Resistance rates among MSSA were highest for ampicillin (70%). The prevalence of MRSA in the hospital increased from 12.5% in 2011 to 20.8% in 2013. Most isolates were associated with infected surgical/burn wounds which may have become infected via the hands of health care workers during dressing exercises. Infection control measures aimed at the proper hand hygiene procedures may interrupt the spread of MRSA. health care workers may also be carriers of MRSA in their anterior nares. Surveillance cultures of both patients and health care workers may help to identify carriers who would be offered antibiotics to eradicate the organisms. Most MRSA are resistant to several non-β-lactam antibiotics. Frequent monitoring of susceptibility patterns of MRSA and the formulation of a definite antibiotic policy may be helpful in decreasing the incidence of MRSA infection.